Plea-Bargaining Law: the Impact of Innocence, Trial Penalty, and Conviction Probability on Plea Outcomes - Wilford, Miko M. (American journal of criminal justice, 2021)
Despite the prevalence of guilty pleas, we know relatively little about factors that influence the decision to plead. Replicating and extending Dervan and Edkins’ Journal of Criminal Law and Criminology , 103, 1-48 . https://doi.org/10.2139/ssrn.2071397, ( 2013 ), we conducted two experiments to examine the effects of guilt status, trial penalty, and conviction likelihood on plea outcomes using an adaptation of a high-stakes cheating paradigm. Students were led to believe that they were participating in a study examining team versus individual problem solving. Those randomly assigned to a guilty condition were induced to cheat on an individual problem by a study confederate (in clear violation of the study instructions). All participants were later accused of cheating in the research study, and were offered the analogue of a plea deal in an academic context. Across both experiments, guilty participants were significantly more likely to plead guilty than innocent participants. In Experiment 2, conviction probability affected plea rates only among the innocent. The trial penalty manipulation had no significant effect on plea rates. Reasons for pleading guilty differed between the innocent and the guilty, whereas the plea rejection rationales were similar across the two groups. Overall, this research highlights several avenues for further research aimed at improving the current system of pleas to reduce false guilty pleas.